Effect of ketamine infusion in treatment resistant depression and in depressive patients with active suicidal ideations: a study from North India - Ubaid Rasool; Neelofer Jan; Zahoor, Marya; Fazle Roub; Rather, Yasir Hassan; Arshad Hussain; Najeeb, Rukhsana (International Journal of Research in Medical Sciences, 2023)
Background: Treatment resistant depression can be a life-threatening condition as it leads to an increase of suicide attempts by two to three folds. It has been estimated that nearly 1 million people die due to suicide every year, and more than two-third of these cases occur when the person is undergoing a major depressive episode. Ketamine is an NMDA receptor antagonist, an anesthetic agent that is short acting and has recently been used as an antidepressant and anti-suicidal agent. It has been seen that a single intravenous infusion of ketamine at a lower dose. i.e., subanesthetic dose of 0.5 mg/kg over a period of 40 minutes produces antidepressant effect which lasts for about a week and various studies have proved that repeated infusions of ketamine can prolong the duration of the antidepressant response. Methods: It was an observational/descriptive study done in the ketamine clinic/ECT suite of institute of mental health and neurosciences Kashmir (an associate hospital of government medical college Srinagar) which runs once a week. In this study, patients satisfying the criteria of TRD and depressive patients with active suicidal ideations, visiting the ketamine clinic who had given a valid informed consent for ketamine infusion enrolled and observed for ketamine efficacy by using specific scales. The study done over a period of 18 months from January 2020 till July 2021. Results: The response rate of ketamine in our study for treatment resistant depression was 70.27%. The response rate of ketamine for suicidality in our study was 63.16%. Our study showed a rapid onset of action for ketamine, two hours after ketamine infusion. Conclusions: A significant fraction of patients suffering from major depressive disorder do not respond to antidepressants and have a poor psychosocial functioning and an increased risk of suicide attempts making their condition life threatening. These patients therefore require special attention to address their underlying condition as well as suicidality to improve their outcome. In this context we studied the role of intravenous ketamine infusion in these patients in improving the psychosocial outcome as well as preventing the suicidal ideation.